2000
DOI: 10.1002/(sici)1097-4652(200003)182:3<366::aid-jcp7>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CXCR-2 but not CXCR-1 expression by human keratinocytes by UVB

Abstract: Interleukin-8 (IL-8) belongs to the CXC chemokine family. IL-8 exerts its biological activities by binding to specific cell surface receptors, CXCR-1 and CXCR-2. Both receptors bind IL-8 with high affinity but they have different affinities for MGSA/Groalpha and NAP-2. It has been shown that the expression of epidermal CXCR-2 is increased in psoriasis, suggesting that activation of KC mediated by CXCR-2 contributes to the characteristic epidermal changes observed in psoriasis. In order to examine the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…IL-8 also exerted mitogenic actions directly or by binding to its receptors on epithelial cells [20,21] . Taken together, it is possible that IL-8, together with other cytokines as well as growth factors [14,22] , could contribute to epithelial cell proliferation even in NERD, and could be eventually linked to carcinogenesis. Again, unlike CXCR-1, CXCR-2 is not specific for IL-8 and can bind to other chemokines such as growth related oncogene α, but it has 2-to 5-fold higher affinity for IL-8 than CXCR-1 [19] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-8 also exerted mitogenic actions directly or by binding to its receptors on epithelial cells [20,21] . Taken together, it is possible that IL-8, together with other cytokines as well as growth factors [14,22] , could contribute to epithelial cell proliferation even in NERD, and could be eventually linked to carcinogenesis. Again, unlike CXCR-1, CXCR-2 is not specific for IL-8 and can bind to other chemokines such as growth related oncogene α, but it has 2-to 5-fold higher affinity for IL-8 than CXCR-1 [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the technique described previously [14] with slight modification, the target sequence of CXCR-1 mRNA was amplified through 35 cycles, each consisting of denaturation at 94 for 30 sec, annealing at 53 for 30 sec and extension at 72 for 30 min, followed by a final extension at 72 for 5 min with specific primers (forward, 5'-CAGATCCACAGA-TGTGGGAT-3' and reverse, 5'-TCCAGCCATTCACCTTG-GAG-3') using an RT-PCR kit (Takara Shuzo Co., Otsu, Japan). Similarly, CXCR-2 mRNA expression was detected under the following conditions: amplification through 35 cycles, each consisting of denaturation at 94 for30 sec, annealing at 60 for 30 sec and extension at 72 for 30 min, followed by a final extension at 72 for 5 min with specific primers (forward, 5'-AGCTGCTCTTCTGGAGGTGT-3' and reverse, 5'-TTAGAGAGTAGTGGAAGTGTGC-3') [14] .…”
Section: Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, they have been found on endodermal, mesenchymal, ectodermal, and neuroectodermal cells. Thus, chemokines may participate in the growth and migration of epithelial cells of the skin (88,118), digestive (51,123) and reproductive (182) tracts, and neuronal and glial cells of the central nervous system (70). Analysis of chemokine receptor expression by leukocytes has revealed that receptor subtypes are expressed to differing degrees by different cell types, thereby dictating their responsiveness to the various chemokines.…”
Section: Chemokine Receptorsmentioning
confidence: 99%
“…Accordingly, their receptors, CXCR1 and CXCR2, originally shown to be expressed in leukocytes, 24 now have been reported on nonhematopoietic cells (e.g., keratinocytes, neurons, neuroendocrine, and oligodendroglial cells). [25][26][27][28][29] More recently, receptors have been described in a variety of embryonic populations. CXCR2 is widely distributed in human tissues including brain (undifferentiated neurons), heart (myocardiocytes), lung (bronchial epithelial cells), liver (hepatocytes), and kidney (early glomeruli and collecting duct).…”
Section: Discussionmentioning
confidence: 99%